2005
DOI: 10.1159/000084751
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Stigmatization Profile in a Cohort of Vitiligo Patients and Effect of the Use of Camouflage

Abstract: Background: Few studies have paid attention to the effects of treatment interventions on the psychosocial consequences of vitiligo. Objectives: To quantify and analyse the psychosocial benefit of the use of camouflage in vitiligo patients. Patients and Methods: 78 vitiligo patients completed the Dermatology Life Quality Index (DLQI) and an adapted stigmatization questionnaire, and 62 of them completed the DLQI after at least a 1-month use of camouflage. Results: The initial mean overall DLQI score (n = 78) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
154
6
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(180 citation statements)
references
References 48 publications
11
154
6
6
Order By: Relevance
“…To date, no universally effective and safe therapy for the disease exists. Many treatment options have been developed, but challenges persist as not all patients respond to the available therapies, relapse is common and complete repigmentation is rarely accomplished [4].…”
Section: Introductionmentioning
confidence: 99%
“…To date, no universally effective and safe therapy for the disease exists. Many treatment options have been developed, but challenges persist as not all patients respond to the available therapies, relapse is common and complete repigmentation is rarely accomplished [4].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that use of camouflage cosmetics can reduce the Dermatology Life Quality Index scores in patients, which means it can improve their quality of life. 7 The higher Dermatology Life Quality Index scores…”
Section: Discussionmentioning
confidence: 99%
“…383 The effect of vitiligo on QoL is often overlooked, 384 although more recent studies have started to address this. 385 …”
Section: Impactmentioning
confidence: 99%